2011
DOI: 10.1103/physreve.84.041926
|View full text |Cite
|
Sign up to set email alerts
|

Exciton transfer dynamics and quantumness of energy transfer in the Fenna-Matthews-Olson complex

Abstract: We present numerically exact results for the quantum coherent energy transfer in the Fenna-Matthews-Olson molecular aggregate under realistic physiological conditions, including vibrational fluctuations of the protein and the pigments for an experimentally determined fluctuation spectrum. We find coherence times shorter than observed experimentally. Furthermore, we determine the energy transfer current and quantify its "quantumness" as the distance of the density matrix to the classical pointer states for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
178
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(193 citation statements)
references
References 43 publications
12
178
3
Order By: Relevance
“…However, previous calculations of 2d-echo spectra of seven-site FMO complex have been often performed with a single-peak Drude-Lorentz spectral density [18,19], and did not yield long-lasting cross-peak oscillations. The situation is different in the population dynamics, which has been analyzed for different spectral densities [26] and yields no significant differences in the duration of population beatings for different spectral density.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous calculations of 2d-echo spectra of seven-site FMO complex have been often performed with a single-peak Drude-Lorentz spectral density [18,19], and did not yield long-lasting cross-peak oscillations. The situation is different in the population dynamics, which has been analyzed for different spectral densities [26] and yields no significant differences in the duration of population beatings for different spectral density.…”
mentioning
confidence: 99%
“…Realistic models of the exciton dynamics in the FMO complex have to include higher order phonon processes as well as the finite time scale of the reorganization process [17]. This requires to go beyond approximative rate equations [23] and non-perturbative techniques [24][25][26][27][28][29][30] are necessary to study the dissipative transfer dynamics.One key parameter determining the duration of coherent oscillations is the spectral density, which encodes the the mode-dependent exciton-bath coupling. The spectral density has important implications for the two contributions to the decoherence rate γ which is the sum of the relaxation rate γ r and the pure-dephasing rate γ d ([33], ch.…”
mentioning
confidence: 99%
“…Recent femtosecond experiments in photosynthetic complexes have revived the interest in the same issues. Oscillatory temporal features in 2D spectra have been initially attributed to electronic coherence but growing evidence indicates that this could be due as well to strongly coupled vibronic motions (37)(38)(39)(40). The simplest approach to energy transfer is based on the Redfield equations that treat the system/bath coupling perturbatively to second order.…”
mentioning
confidence: 99%
“…A number of microscopic models have been developed and their studies highlight the possibility of quantum coherence playing an important role in, for example, the energy and charge transfer process in mesoscopic bio-chemical systems [1][2][3][4][5][6][7] or artificial photosynthetic complexes [8,9]. At the same time first experimental studies have shown that quantum coherence can play a significant role in photosynthetic light-harvesting complexes [10][11][12] and in chromophoric energy transport [13].…”
Section: Introductionmentioning
confidence: 99%